Bank Resolution Costs, Depositor Preference, and Asset Encumbrance - Hardy, Daniel (IMF Working Papers; Working Paper ;, 2013)
Depositor preference and collateralization of borrowing may reduce the cost of settling the conflicts among creditors that arises in case of resolution or bankruptcy. This net benefit, which may be capitalized into the value of the bank rather than affect creditors' expected returns, should result in lower overall funding costs and thus a lower probability of distress despite increasing encumbrance of the bank's balance sheet. The benefit is maximized when resolution is initiated early enough for preferred depositors to remain fully protected.